Multirate digital control system implementation - Ushama, Imama Karim Manba (Kuliyyah of Engineering, International Islamic University Malaysia, 2016)
The purpose of this study is to investigate and to demonstrate the multirate digital controller through the use of Digital Signal Processor (DSP). The complexity in the multirate controller as well its benefits are presented. The hardware limitations that results when two or more systems of different bandwidths in a controllable closed control system has been an issue in many fields. This prevents a control algorithm to be operated at the maximum sampling time. Two types of controllers (stable and marginally stable) for multirate system have been designed and implemented. An analysis is done to find an optimal sampling time and the effects of over-sampling as well as under-sampling has been presented. The scope of this work is to explore one type of multirate system only and implement it into two different types of systems, a second order filter and the hard disk drive (HDD). These systems represent a stable and a marginally stable system with two types of controllers being used. Since direct simulation (using Simulink) cannot be used since Simulink is built for single rate system only, a simulation using numerical methods is setup by the author. A prototype of the filter is setup and the controller is tested directly while the HDD is tested using a Hardware in Loop (HIL) method. The experiments are carried out using the DSP. Settling time improvement and steady state error improvement has been achieved by implementing the multirate controller. The improvement depends on the 'N' factor which depends on the sampling time. The application of the multirate controller can be seen in Hard Disk Drives (HDD), Image Processing, and Satellite Systems.